Indirect positive directive verbs between Arabic and Turkish - Ali, Nouray Omer; Dzaey, Dilkhosh Jarallah Hussein (Zanco Journal of Human Sciences, 2023)
One of the most significant areas of contemporary linguistics is comparative pragmatic study, which examines the similarities and differences between two different languages as well as all the data and achievements related to it. The significance of the current academic paper entitled (Indirect positive directive verbs between Arabic and Turkish) to treat all the categories of speech that fall within the indirect directive verbal acts of the command, negative, interrogative and warning directive verbal acts, by presenting its structures and non-verbal contents, explaining how they are used and the types of external attitudes to identify their indirect meanings, which are known as pragmatic capabilities. The current study is a joint study between language and literature because it explains two things: the first is the direct meaning of the word and the second is the indirect request that we are talking about, this has various meanings in Arabic and Turkish, including (social, intellectual, psychological and others), this is reflected in the context in which the speech is made. The statement may be a pragmatic example taken from the mouths of people or from the Holy Qur'an or from a piece of poetry that is presented with an indirect purpose. Ideas then change from their direct graphic meanings to indirect desired meanings, then to linguistic elements to observe oral sound structures, sentence content, and affective verbs, according to Searle's classification of indirect directive verbs in general. The purpose of identifying the content of the verbal action is directed to the listener in order to influence him. Finally, the discussion reaches the most important conclusions related to the subject of our discussion.